Rational synthesis of α-hydroxyphosphonic derivatives including dronic acids. (27th May 2019) - Grün, Alajos; Rádai, Zita; Sőregi-Nagy, Dávid Illés; Greiner, István; Keglevich, György
Abstract: New, green methods have been elaborated for the syntheses of α-hydroxyphosphonates and α-hydroxymethylenebisphosphonic derivatives (HMBPs, dronates). α-Hydroxyphosphonates were prepared via the Pudovik reaction, while the synthesis of HMBPs has been performed in the three-component reaction of carboxylic acids, phosphorus trichloride and phosphorus acid. Graphical Abstract: UF0001